Pemenuhan Aspek Legalitas Sertifikat Produksi Pangan Industri Rumah Tangga (SPP-IRT) UMKM Ibu Nia Dan KWT Karya Lestari - Trisna, Findie Heka (LPPM Universitas Timor, 2024)
Good Food Production Practices for Home Industry (CPPB-IRT) is one of the important factors to meet quality standards or food safety requirements set for food. CPPB-IRT is a guideline that has requirements in every scope or aspect that must be met by proper, safe and quality Home Industry Food producers (PIRT). The purpose of this assistance is to provide assistance in preparing the requirements and fulfilling the legality of SPP-IRT and the application of CPPB-IRT to UMKM Ibu Nia and KWT Karya Lestari in Kutai Kartanegara Regency. The method used in this assistance is 1) observing the two MSMEs, 2) providing assistance and application to the two MSMEs, and 3) registering the SPP-IRT. The results of the assistance to the two MSMEs showed good changes in implementing CPPB-IRT and obtaining SPP-IRT as legality.